The Role of the Melatoninergic System in Circadian and Seasonal Rhythms—Insights From Different Mouse Strains - Pfeffer, Martina; von Gall, Charlotte; Wicht, Helmut; Korf, Horst-Werner (Frontiers in Physiology, 2022)
The melatoninergic system comprises the neurohormone melatonin and its molecular targets. The major source of melatonin is the pineal organ where melatonin is rhythmically produced during darkness. In mammals, melatonin biosynthesis is controlled by the central circadian rhythm generator in the suprachiasmatic nucleus (SCN) and nonvisual photoreceptors in the retina. Melatonin elicits its function principally through two specific receptors called MT1 and MT2. MT1 is highly expressed in the SCN and the hypophysial pars tuberalis (PT), an important interface for control of seasonal functions. The expression of the MT2 is more widespread. The role of the melatoninergic system in the control of seasonal functions, such as reproduction, has been known for more than four decades, but investigations on its impact on the circadian system under normal (entrained) conditions started two decades later by comparing mouse strains with a fully functional melatoninergic system with mouse strains which either produce insufficient amounts of melatonin or lack the melatonin receptors MT1 and MT2. These studies revealed that an intact melatoninergic system is not required for the generation or maintenance of rhythmic behavior under physiological entrained conditions. As shown by jet lag experiments, the melatoninergic system facilitated faster re-entrainment of locomotor activity accompanied by a more rapid adaptation of the molecular clock work in the SCN. This action depended on MT2. Further studies indicated that the endogenous melatoninergic system stabilizes the locomotor activity under entrained conditions. Notably, these effects of the endogenous melatoninergic system are subtle, suggesting that other signals such as corticosterone or temperature contribute to the synchronization of locomotor activity. Outdoor experiments lasting for a whole year indicate a seasonal plasticity of the chronotype which depends on the melatoninergic system. The comparison between mice with an intact or a compromised melatoninergic system also points toward an impact of this system on sleep, memory and metabolism.